Pembangunan Sistem Mobile Aplikasi Scholarship Kamajaya - Gde Rama Vedanta Yudhistira; Dewi, Findra Kartika Sari; Wilfridus Bambang Triadi Handaya (Jurnal Informatika Atma Jogja, 2024)
The KAMAJAYA Scholarship Application Information System (ASOKA) website has notable shortcomings, including an unresponsive design and limited functionality that fails to meet all user needs. These issues make it less accessible on mobile devices and less popular among users. To address these challenges, the author proposes a mobile version of ASOKA, developed using Flutter. The mobile application retains the core features of the ASOKA website but is optimized for mobile devices and includes new features such as room schedule management, activity points tracking, and notifications to enhance user engagement. The study's findings indicate that the ASOKA mobile application is an effective alternative for managing KAMAJAYA Scholarship data. Moreover, the added features successfully address the unmet needs of scholarship recipients, while the notification system improves the speed and accuracy of information delivery. Situs Sistem Informasi Aplikasi Scholarship KAMAJAYA (ASOKA) memiliki kekurangan, seperti tampilan yang tidak responsif dan belum mengakomodasi seluruh kebutuhan pengguna, menyebabkan sulit digunakan pada perangkat mobile dan kurang diminati. Untuk mengatasi hal ini, penulis mengusulkan solusi berupa sistem ASOKA mobile yang dibangun menggunakan Flutter. Aplikasi ini memiliki fitur yang sama dengan situs ASOKA namun dirancang khusus untuk perangkat mobile, serta dilengkapi fitur baru seperti pengelolaan jadwal ruang, poin keaktifan, dan notifikasi untuk meningkatkan keterlibatan pengguna. Hasil penelitian menunjukkan bahwa ASOKA mobile efektif sebagai alternatif untuk pengelolaan data pada KAMAJAYA Scholarship, dan fitur baru yang ditambahkan berhasil memenuhi kebutuhan penerima beasiswa yang belum terakomodasi oleh situs ASOKA. Notifikasi juga membantu pengguna mendapatkan informasi dengan lebih cepat dan akurat.